Rurality and the people-centric approach to public service delivery in the digital age–a study of South African rurality as a proxy for low- and middle-income country contexts - Pashapa, Tapfuma (Department of Information Systems, 2026)
Based on a pragmatist worldview, I employed an exploratory sequential mixed-methods research design to enhance our understanding of the public value of information and communication technology (ICTs) and the nature of services delivered in low- and middle-income settings. Understanding the intricate relationship between rurality, ICT expansion, and service delivery in low- and middle-income settings is imperative for tailoring technology-driven strategies to rural areas within the constraints of limited resources. While some e-service delivery initiatives have succeeded, their overall effectiveness remains mixed. Further research is needed to achieve universal coverage and enhance functionality beyond basic communication for more meaningful use. This study is motivated by the need to explore how the quality of rural amenities—an indicator of rurality—intersects with the proliferation of ICTs as a driver of transformation and development. Additionally, recent studies have pointed to the importance of rurality measures that reflect peripherality, adjacency, contextuality, and demographic characteristics. South African rurality measures in particular could be enhanced by incorporating factors such as contiguity, flows, poverty, and service accessibility. In the qualitative phase of the study, I gleaned insights from official documents, reports, research articles, and interviews. The study was grounded on service-dominant approaches to new public management (NPM) models, based on theoretical underpinnings drawn from public value and information asymmetry theories. NPM underscores the significance of understanding the role and impact of ICTs on service-dominant approaches. I adopted the digital divide model and the communication for development (C4D) framework to develop data collection instruments and to evaluate development communication. Despite challenges posed by the sparse population distribution hindering the effectiveness of digital service provision and discouraging service providers from establishing relevant communication infrastructure, I found that the value of digital service provision in rural areas primarily manifests in reduced distances and the time required to access intangible services. Utilising the 2011 South African census data and other contemporaneous datasets, I developed spatial rurality indexes using JRC-EC's index development procedure and the procedures used in other studies. Underdeveloped and remote regions exhibited significantly greater access to public healthcare and education services, which were particularly well-suited to the advantages offered by ICTs. In the context of ICT proliferation, my findings suggest that the economics of service delivery information tend to favour service providers and those who are socioeconomically advantaged, resulting in varying benefits, particularly for service consumers. This information imbalance arises from the power wielded by service providers, stemming from their ownership of ICT-based C4D spaces and advantages in overseeing service delivery processes. Affordable, user-friendly, and accessible technologies, particularly mobile phones, mobile-based applications, and mass media, primarily functioned as information disseminators, repositories of knowledge, and communication tools for marginalised rural service consumers. Hence, I argue that the benefits of information asymmetry for consumers are minimised. These benefits are not directly tied to their utilisation of publicly available service delivery information, which is meant to provide transparency and enhance their participation and oversight of service delivery processes. Instead, access to the information by other actors such as central government may enforce these advantages. It is crucial to acknowledge that ICT-based development communication in low- and middle-income contexts primarily facilitates a top-down information flow, with service consumers mainly participating in service delivery by providing information to support service delivery processes.